The Implementation of Higher Order Thinking Skills (HOTS) in English Language Teaching: The Case of Indonesian Senior High School EFL Teachers - Mhd Lutfi Brilian Dima; Daflizar - Daflizar; Ahmadi Ahmadi (ELT Worldwide: Journal of English Language Teaching, 2021)
The purpose of this research is to explore teachers' perceptions of the implementation of Higher Order Thinking Skills (HOTS) in English language classrooms. Specifically, it attempted to explore: (1) teachers’ understanding of HOTS, (2) teachers’ perceptions of the implementation of HOTS in EFL classrooms, and (3) teachers’ perceived obstacles in the implementation of HOTS. The research used a qualitative approach with a case study design. Five English language teachers at a senior high school in Jambi Province, Indonesia participated in this study. Semi-structured interviews were employed to collect the data. The data were analyzed following Miles and Huberman's (1994) qualitative data analysis procedures. The results revealed that all participants had a good understanding of the concept of HOTS. The definitions of HOTS given by all the participants were related to the sub-skills of Bloom's Taxonomy. All the participants have also implemented HOTS in the English language teaching and learning process. However, the implementation has yet to be effective due to some obstacles, which include students' low English proficiency, teachers' lack of competencies, and limited supporting facilities such as internet access, learning media, and learning sources.